Composition and Diversity of Understory Plants in Agathis labillardierei Stands in the Sorong Nature Park Forest, West Papua - Ponisri Ponisri; Muzna A.A Gafur; Rahasela Savira Ulim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the species composition, diversity, dominance, and evenness of deciduous understory plant species in Agathis labillardierei stands in the Sorong Nature Park Forest, West Papua. The survey method used was plot sampling in Agathis labillardierei stands of various ages. The results of the study showed that there were 37 species of understory plants distributed across 25 families, including Araceae, Fabaceae, Poaceae, Piperaceae, Euphorbiaceae, Zingiberaceae, Acanthaceae, Urticaceae, Verbenaceae, Solanaceae, Bromeliaceae, Pteridaceae, Gleicheniaceae, Orchidaceae, Myrtaceae, Athyriaceae, Ophioglossaceae, Rubiaceae, Pandanaceae, Asteraceae, Marantaceae, Schizaeaceae, Dennstaedtiaceae, Thelypteridaceae, and Araucariaceae. The diversity index of understory plants was classified as moderate, with a value of 1.497; the dominance index was low, at 0.037; and the evenness index was 0.954. These findings indicate that the understory plant community in Agathis labillardierei stands is in a relatively ecologically stable condition, with a high level of evenness that contributes to the stability of species diversity.